2016
DOI: 10.1016/j.cub.2016.01.064
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Plasticity in Somatosensory Cortex Supports Motor Learning by Observing

Abstract: Summary An influential idea in neuroscience is that the sensory-motor system is activated when observing the actions of others [1,2]. This idea has recently been extended to motor learning, in which observation results in sensory-motor plasticity and behavioral changes in both motor and somatosensory domains [3–9]. However, it is unclear how the brain maps visual information onto motor circuits for learning. Here we test the idea that the somatosensory system, and specifically primary somatosensory cortex (S1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 34 publications
8
51
2
Order By: Relevance
“…Unlike what has been shown in experiments of reaching adaptation (Mattar and Gribble, 2005;McGregor et al, 2018McGregor et al, , 2016Williams and Gribble, 2012), we did not observe a significant effect of observational learning on locomotor adaptation. Though the comparisons between the Observational and Control group did not reach statistical significance, we noted modestly faster learning in the Observational group that occurred later in the learning curve.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike what has been shown in experiments of reaching adaptation (Mattar and Gribble, 2005;McGregor et al, 2018McGregor et al, , 2016Williams and Gribble, 2012), we did not observe a significant effect of observational learning on locomotor adaptation. Though the comparisons between the Observational and Control group did not reach statistical significance, we noted modestly faster learning in the Observational group that occurred later in the learning curve.…”
Section: Discussioncontrasting
confidence: 99%
“…In our third experiment, we asked whether active movement was necessary for locomotor learning. Given prior observations in reach adaptation (Mattar and Gribble, 2005;McGregor et al, 2016;Williams and Gribble, 2012), we expected that people could also learn a new walking pattern by watching someone else adapt their gait.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while watching the smooth suturing movements of an expert surgeon, the sensorimotor areas of the brain responsible for those same movements are activated, such that subsequent reproduction of those movements by the observer is facilitated. In this way, mirror neurones may represent the mechanism for the perceptual blueprint 7,8 created during observational learning 18,22,23 .…”
Section: Mirror Neurone Systemmentioning
confidence: 99%
“…However, it remains unclear how visual signals are mapped onto motor circuits for such learning to occur. Indeed, our understanding of how action representations develop during motor learning through physical compared to observational practice remains in its infancy (Frey & Gerry, 2006;Hodges et al, 2007;Ostry & Gribble, 2016;McGregor et al, 2016;Vogt et al, 2007). Here we advance understanding of observational learning by using functional magnetic resonance imaging (fMRI) to test the idea that observational learning of action sequences leads to distinctive patterns of activity in sensorimotor cortices, in a manner similar to that reported following physical practice .…”
Section: Introductionmentioning
confidence: 92%
“…Common brain regions have been shown to underpin motor learning following physical and observational experience (Cross et al, 2009;Kirsch & Cross, 2015;Ostry & Gribble, 2016). For example, if the motor system is engaged in another task (Mattar and Gribble, 2005) or if sensorimotor systems are disrupted through non-invasive stimulation (Brown et al, 2009;McGregor et al, 2016), observational learning is reduced. Further, neuroimaging studies have demonstrated that frontoparietal cortex shows similar changes in magnitude and connectivity when learning through physical and observational practice (Cross et al, 2009;Vogt et al, 2007;Higuchi et al, 2012;Sakreida et al, 2018;van der Helden et al, 2010).…”
Section: Introductionmentioning
confidence: 99%